Free composite groin flap to solve a complex loss of tissue in a traumatic injury of the foot: A case report. (December 2018) - Daghino, W.; Aprato, A.; Bistolfi, A.; Filipponi, M.; Battiston, B.; Massè, A.
Abstract: Severe traumatic losses of soft tissues and bone at foot and ankle level are often treated by means of amputation, but this may involve important psychological and anatomic consequences for the patient. If there are good vascular conditions, reconstruction by means of composite free flaps is often the only alternative to this demolitive treatment. The transfer of composite free flaps that include vascularized bone from various donor sites may provide anatomical reconstruction and recovery of function of the foot and ankle. If plantar skin and its sensation are present, these techniques may represent a good choice in the treatment of complex injuries of the foot, and by means of skeletal morphological reconstruction, they may give good functional results. With these premises, we report a case in which was used a groin flap to fill and solve a complex defect of bone and soft tissues of midfoot in a gunshot injury.